On a characteristic property of distributions related to the Laplace - Jones, M. C. (South African Statistical Journal, 2019)
It is shown that the asymmetric Laplace distribution uniquely arises as the distribution of both a difference between independent positive random variables and of a random choice between those random variables, one of them having been given a negative sign. Related results on the positive half-line are also given.